A comprehensive modeling study of particulate coalescence and breakup mechanisms in solid propellant motor nozzles. (August 2022) - Park, Ki Sun
Highlights: A comprehensive model addressing particle growth or decay by particle collision and breakup in solid motor nozzles is developed. The predicted particle sizes agree well with the correlation in the previous study. The particle growth mainly occurs in an area close to the throat across the converging and diverging sections. The breakup process is balanced with the collision process in the diverging section. A large inlet particle size does not always result in a large exit particle size due to the breakup process. Abstract: Gas-particle flows are modeled to account for the coalescence and breakup of liquid aluminum oxide particles dispersed within the gas phase in solid propellant motors. The one-way coupled population balance equation, which addresses a change in number concentration of particles by the particle to particle and surrounding to particle interactions, is solved using the direct quadrature method of moments (DQMOM). Simulations are performed on the converging-diverging nozzles attached to solid propellant motors and the mass mean diameter at the nozzle exit is compared to previous measurements and a correlation derived from numerous existing measurements data. The results from a series of simulations are presented to assess the effects of chamber pressure, initial particle concentration and size, and nozzle scale on resulting particle size growth.